Language and Identity in Stand-up Comedy: A Discourse Analysis of Humor - Rosmaria, Rosmaria (PT. Anagata Sembagi Education, 2025)
This study explores the intersection between language, identity construction, and humor in the context of stand-up comedy using a critical discourse analysis approach. Stand-up comedy, as a popular cultural genre, is not merely a medium of entertainment but also a site where social meanings are created, contested, and negotiated. The research focuses on how comedians utilize linguistic strategies such as code-switching, the use of slang, metaphor, and local idioms to represent and perform multiple social identities, including those related to ethnicity, gender, and class. Through analyzing selected performances by Indonesian comedians, the study reveals that humor functions as a powerful discursive tool that reflects social realities, challenges dominant ideologies, and facilitates symbolic resistance. Furthermore, audience reactions such as laughter, silence, or applause are shown to co-construct the meaning of humor and identity on stage. The study concludes that stand-up comedy serves as a critical platform for negotiating cultural norms and identities within contemporary public discourse, contributing significantly to linguistic and cultural studies.